2018
DOI: 10.1101/485250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of fear generalization by the zona incerta

Abstract: Fear expressed towards threat-associated stimuli is an adaptive behavioral response. In contrast, the generalization of fear responses toward non-threatening cues is maladaptive and a debilitating dimension of trauma-and anxiety-related disorders. Expressing fear to appropriate stimuli and suppressing fear generalization requires integration of relevant sensory information and motor output. While thalamic and sub-thalamic brain regions play important roles in sensorimotor integration, very little is known abou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 56 publications
4
31
0
Order By: Relevance
“…Interestingly, our trans-synaptic tracing results demonstrated a ZI-to-CeA PKC-δ + neural circuit (Table S1). Stimulation of the ZI can be used to treat fear generalization [ 52 ]. Combined with recent findings on the functions of the ZI (eating, hunting, and sleeping) [ 53 ] and the role of CeA PKC-δ + neurons in conditioned fear [ 17 , 30 ], these novel projections may provide another explanation for how the ZI reacts in fear modulation and extend the potential roles of the amygdala in different functions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our trans-synaptic tracing results demonstrated a ZI-to-CeA PKC-δ + neural circuit (Table S1). Stimulation of the ZI can be used to treat fear generalization [ 52 ]. Combined with recent findings on the functions of the ZI (eating, hunting, and sleeping) [ 53 ] and the role of CeA PKC-δ + neurons in conditioned fear [ 17 , 30 ], these novel projections may provide another explanation for how the ZI reacts in fear modulation and extend the potential roles of the amygdala in different functions.…”
Section: Discussionmentioning
confidence: 99%
“…We found similar results in hub identification, which identified mostly different brain areas in all groups, but also a disengagement of the neocortical nodes and engagement of the thalamic nodes as a response to exposure to UCMS. Interestingly, the only hub identified in the UCMS TAM group is the Zona Incerta (ZI), a brain area with roles in central pain, compulsions and Parkinson's disease (Mallet et al, 2002;Masri et al, 2009) that has only recently been shown to modulate fear generalization (Venkataraman et al, 2019). In the graph analysis, we found that our constructed networks of all groups have a small-world topology, like many real-world networks.…”
Section: Discussionmentioning
confidence: 79%
“…Increasing the intensity of the US is one of the most reliable parameters for promoting generalized responding. Numerous studies have shown that increasing the intensity of the US increases generalization (Baldi, Lorenzini, & Bucherelli, ; Ghosh & Chattarji, ; Venkataraman et al., ). For instance in mice, “weak” US intensities from 0.3 to 0.5 mA results in CS+ discrimination, while 0.8‐ to 1.0‐mA US intensity promoted generalization (Ghosh & Chattarji, ).…”
Section: Commentarymentioning
confidence: 99%
“…For these reasons, Pavlovian fear conditioning is currently a leading model for studying circuity thought to be dysregulated in PTSD. Numerous brain systems have been demonstrated to contribute to fear discrimination and generalization processing, including the cingulate cortex (Ortiz et al., ), hippocampus (Besnard & Sahay, ), amygdala (Ciocchi et al., ; Ghosh & Chattarji, ; Grosso, Santoni, Manassero, Renna, & Sacchetti, ), thalamic and subthalamic nuclei (Ferrara, Cullen, Pullins, Rotondo, & Helmstetter, ; Ramanathan, Ressler, Jin, & Maren, ; Venkataraman et al., ; Xu & Sudhof, ), midbrain (Rozeske et al., ), and prefrontal cortices (Fitzgerald et al., ; Pollack et al., ; Rozeske et al., ; Scarlata et al., ). For a review on the neurobiology of fear generalization, see Asok, Kandel, and Rayman () and Sangha, Diehl, Bergstrom, and Drew ().…”
Section: Introductionmentioning
confidence: 99%